Usefulness of ultrasound examination in the evaluation of ulnar nerve impairment in the course of supracondylar fracture - a case report - Magdalena Tercjak-Rećko; Tomasz Guszczyn; Jerzy Andrzej Wojnar; Ewelina Kwiatkowska; Adam Hermanowicz (Kazimierz Wielki University, 2018)
Impairments of the ulnar nerve in the courses of supracondylar fractures of the humerus (SCHF) are one of the most common complications after elbow fractures in children. A 6-years-old girl presented to the Emergency Department with the complaint of pain and reduced range of motion of the left elbow after  fell on the flexed elbow. The diagnosis was supracondylar fractures of the left humerus. The patient had symptoms of paresis of the ulnar nerve after  treated by closed reduction with using K-wires and immobilization in an over-elbow plaster cast. The decision to "watch and wait" was made taking into account clinical condition, findings in additional examinations, especially US. Ultrasound examinations helped to avoid unnecessary surgical treatment. After around ten months, complete resolution of symptoms was achieved. The patient recovered well.